Conditional dependence between oil prices and exchange rates in BRICS countries: An application of the copula-GARCH model - Yijin He; Shigeyuki Hamori (Journal of Risk and Financial Management, 2019)
We studied the dependence structure between West Texas Intermediate (WTI) oil prices and the exchange rates of BRICS1 countries, using copula models. We used the Normal, Plackett, rotated-Gumbel, and Student's t copulas to measure the constant dependence, and we captured the dynamic dependence using the Generalized Autoregressive Score with the Student's t copula. We found that negative dependence and significant tail dependence exist in all pairs considered. The Russian Ruble (RUB)-WTI pair has the strongest dependence. Moreover, we treated five exchange rate-oil pairs as portfolios and evaluated the Value at Risk and Expected Shortfall from the time-varying copula models. We found that both reach low values when the oil price falls sharply.
Keywords: 330; exchange rate; oil price; BRICS; dependence structure; copula